DISTRIBUTION OF BENTHIC FORAMINIFERA IN THE WATERS FROM OFF PUTRI ISLAND, NORTHERN BATAM, RIAU ARCHIPELAGO - Resti Samyati Jatiningrum; Anggun Mutika; Luli Gustiantini; Nineu Yayu Gerhaneu; Godwin Latuputty; Agustina Rosi Divina (BULLETIN OF THE MARINE GEOLOGY, 2022)
Putri Island is the outermost island bordering Singapore, located north of Batam City, Riau Archipelago Province. A total of 29 sediment samples were collected from the seafloor off Putri Island for foraminiferal study. The purpose of this study is to determine their abundance and distribution related to previous data of environmental conditions. For this study, we analysed quantitative analysis of benthic foraminifera including its abundance, diversity, dominance, and evenness indices. The results denoted that benthic foraminifera was composed of 62 species that belonged to 31 genera. The diversity index was categorized as a moderate to high diversity index (1.85-3.12), with a low to high evenness index (0.37 – 0.78), and a low dominance index (0.05-0.24). This indicates that in general the waters of Putri Island are considered to have a fairly good environment and are quite stable for foraminiferal growth. A slight environmental stability degradation occurred in the north eastern part of the study area which demonstrates high levels of pollutants in the waters. This situation influent the benthic assemblages which are indicated by lowering index diversity at that location.